2018
DOI: 10.1002/acr.23578
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in the Incidence of Primary Chronic Cutaneous Lupus Erythematosus in the Southeastern US: The Georgia Lupus Registry

Abstract: Our findings underscore striking racial disparities in the susceptibility for primary CCLE, with black people experiencing between three and five-fold increased incidence of CCLE in general and DLE in particular, compared to white people. Gender differences were consistent with those reported previously, with a three times higher risk of DLE in females compared to males. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 34 publications
5
43
0
2
Order By: Relevance
“…The Swedish study provided a pDLE rate of 3.2 per 100 00018 while the study from French Guiana, with a predominantly African population, reported an annual chronic CLE incidence of 2.6 per 100 000 population (of which 90% were pDLE) 19. In line with our findings, both the Minnesota study as well as the Swedish study found that prevalent and incident pDLE were higher among women compared with men and most common in middle-aged women 7 17 18. The Minnesota study also reported rates of CLE by race/ethnicity,17 but these rates are not comparable given the predominantly white population (90.3%) included in that analysis.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The Swedish study provided a pDLE rate of 3.2 per 100 00018 while the study from French Guiana, with a predominantly African population, reported an annual chronic CLE incidence of 2.6 per 100 000 population (of which 90% were pDLE) 19. In line with our findings, both the Minnesota study as well as the Swedish study found that prevalent and incident pDLE were higher among women compared with men and most common in middle-aged women 7 17 18. The Minnesota study also reported rates of CLE by race/ethnicity,17 but these rates are not comparable given the predominantly white population (90.3%) included in that analysis.…”
Section: Discussionsupporting
confidence: 85%
“…Our more restrictive secondary definition required evidence that the diagnosis was stated by a rheumatologist or dermatologist. Given the MLSP did not approach dermatology practices and only rarely had access to hospital-associated dermatology clinics as a case-finding source, we did not want to further underestimate the burden of DLE by also requiring evidence of a biopsy, which is not always performed 7. Thus, we did not require evidence of a compatible diagnostic biopsy for either definition.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence and severity of some autoimmune skin diseases can vary depending on gender, age, and ethnicity of the population . Previous studies of connective tissue diseases, particularly discoid lupus erythematosus (DLE), have shown a predilection for patients of African descent, and black patients have been shown to experience skin damage early in their disease course …”
Section: Introductionmentioning
confidence: 99%